2007
DOI: 10.1136/thx.2006.065557
|View full text |Cite
|
Sign up to set email alerts
|

Should pulmonary embolism be suspected in exacerbation of chronic obstructive pulmonary disease?

Abstract: Background: The cause of acute exacerbation of chronic obstructive pulmonary disease (COPD) is often difficult to determine. Pulmonary embolism may be a trigger of acute dyspnoea in patients with COPD. Aim: To determine the prevalence of pulmonary embolism in patients with acute exacerbation of COPD. Methods: 123 consecutive patients admitted to the emergency departments of two academic teaching hospitals for acute exacerbation of moderate to very severe COPD were included. Pulmonary embolism was investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
3
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 20 publications
5
70
3
10
Order By: Relevance
“…In addition to high rates of atherothrombotic arterial cardiovascular events in COPD, as described in previous sections, there is also some evidence of excess venous thromboembolism mainly during acute exacerbations, although prevalence varies widely in the literature [64,65].…”
Section: Hematological Coagulopathy Polycythemia and Anemiamentioning
confidence: 99%
“…In addition to high rates of atherothrombotic arterial cardiovascular events in COPD, as described in previous sections, there is also some evidence of excess venous thromboembolism mainly during acute exacerbations, although prevalence varies widely in the literature [64,65].…”
Section: Hematological Coagulopathy Polycythemia and Anemiamentioning
confidence: 99%
“…Decreased cardiac output reduces oxygen delivery to respiratory muscles, contributing to respiratory decompensation in patients with COPD (1,24). Pulmonary embolism is an uncommon trigger for acute exacerbation (31), although in patients with acute exacerbation of unknown origin, the prevalence may be as high as 25% (32). Other conditions, such as nonpulmonary infections and pneumothorax, can mimic an acute exacerbation or possibly act as triggers (1)(2)(3).…”
Section: Etiology and Confounding Factorsmentioning
confidence: 99%
“…12 In contrast, a recent study reported a low incidence of PE in patients hospitalized for acute exacerbation of COPD: 6.2% of patients with a clinical suspicion of PE, and only 1.3% of those with low suspicion. 13 A meta-analysis found that the prevalence of PE in acute exacerbations of COPD was 19.9%. 14 Our study identified a small cohort of participants (5.7%) with VTE, which is consistent with some studies with similar prevalence rates.…”
Section: Discussionmentioning
confidence: 99%